Synergistic effects of ethanol medicinal plant extracts with erythromycin against skin strains of staphylococci with inducible phenotype of MLS-resistance - Yurchyshyn, O; Rusko, H; Kutsyk, R (Annals of Mechnikov’s Institute, 2019)
Introduction. One of the main ways to control microorganisms’ resistance to antibiotics is to find substances that are able to overcome it and potentiate antibiotics action, in particular to neutralize the antibiotic-inactivating enzymes or block the active efflux of antibiotic from microbial cells. Every year there is a growing interest in the therapeutic potential of herbal active compounds as modifiers of antibiotic resistance including MLS-resistance (macrolide-lincosamide-streptoramin B).It should be emphasized that a number of biologically active substances of plant origin can potentiate antimicrobial activity of erythromycin (ERY) against MLS-resistant staphylococci. The present study was designed to investigate the antibacterial and synergistic effects of eight Ukrainian ethanol medicinal plant extracts with erythromycin against skin strains of staphylococci with inducible phenotype of MLS-resistance. Material & methods.S. aureus and S. epidermidis strains were tested for susceptibility to antibiotics of MLS-group by disk diffusion test. Effective antimicrobial concentrations of plant extracts and erythromycin were determined by two-fold serial dilution in nutrient agar and broth. Combinatory effects between organic extracts and ERY were assessed using the checkerboard assay against tested strains to evaluate culture growth in the presence of two antimicrobials with different concentrations. Results & discussion. The Alnus incana L.fruits extract was the most potent inhibitor against tested strains (MIC 40.625-162.5 µg/mL); whileGeraniumpratenseL. rhizomes extract exhibited the least antimicrobial activity (MIC 650-2,600 µg/mL). The Alnus incana L.fruits extract and the GeraniumpratenseL. rhizomes extract showed synergistic effect with erythromycin against 100% strains of staphylococci (average FICI 0.028 – 0.057; p<0.001). In the presence of 1/4MIC of ERY Alnus incana L.fruits extract antimicrobial concentration was decreased in 32-64 times and GeraniumpratenseL. rhizomes extract antimicrobial concentration was decreased in 64-256 times.Ethanol extracts of Betula verrucosa L.buds(averageFICI 0.473±0.20), Arctostaphylosuva-ursi (L.) Spreng. leaves (average FICI 0.143±0.18) andTamarixramosissimaLedeb. leaves (average FICI 0.189±0.29) showedsynergic action with erythromycin against 71.4-85.7% tested strains. Ethanol extracts of SanguisorbaofficinalisL. roots showed non-interactive action with antibiotic against 42.8% isolates of staphylococci. Additive interaction with erythromycin for this extract was observed against 28.6% and synergic action against 28.6% strains (averageFICI 0.812±0.52).Biotaorientalis (L.) Endl. (Platycladusorientalis (L.) Franco) fruitsextract and Cotinus coggygria Scop. (Rhus cotinus R.) leaves extract exhibited non-interactive action with antibiotic against all tested strains (averageFICI 2.0±0.0). Experimental data indicate that combination of plant extracts with macrolides in therapeutic regimens against MLS-resistant staphylococci is promising, particularly for the treatment of pyoderma. The introduction of combined chemotherapy in clinical practice can actually help to solve two problems of modern medicine - slow the process of microorganisms (such as staphylococcus) resistance to antibiotics acquiring and improve treatment of infections caused by resistant strains. Detection of bacteria antibiotic resistance modifiers in various plants stimulates to their intensive phytochemical study for isolation and identification of the active components. It will help to investigate the mechanisms of synergy on the molecular level. Conclusion. BAC of medicinal and aromatic plants potentiate antimicrobial activity of macrolides against skin isolates of staphylococci with inducible MLS-resistance. Alnus incana L. fruits ethanolic extract demonstrates the best direct antimicrobial activity and in combination with ERY synergistically inhibits the growth of S. aureus and S. epidermidisMLS-resistant strains. Ethanolic extracts of Geranium pratense L. rhizomes, Arctostaphylos uva-ursi (L.) Spreng. leaves, Tamarix ramosissima Ledeb. leaves and Betula verrucosa L. buds also exhibit synergistic effect with ERY against skin isolates of s